Combined Radiochemotherapy: Metalloproteinases Revisited - Waller, Verena; Pruschy, Martin (Frontiers in Oncology, 2021)
Besides cytotoxic DNA damage irradiation of tumor cells triggers multiple intra- and intercellular signaling processes, that are part of a multilayered, treatment-induced stress response at the unicellular and tumor pathophysiological level. These processes are intertwined with intrinsic and acquired resistance mechanisms to the toxic effects of ionizing radiation and thereby co-determine the tumor response to radiotherapy. Proteolysis of structural elements and bioactive signaling moieties represents a major class of posttranslational modifications regulating intra- and intercellular communication. Plasma membrane-located and secreted metalloproteinases comprise a family of metal-, usually zinc-, dependent endopeptidases and sheddases with a broad variety of substrates including components of the extracellular matrix, cyto- and chemokines, growth and pro-angiogenic factors. Thereby, metalloproteinases play an important role in matrix remodeling and auto- and paracrine intercellular communication regulating tumor growth, angiogenesis, immune cell infiltration, tumor cell dissemination, and subsequently the response to cancer treatment. While metalloproteinases have long been identified as promising target structures for anti-cancer agents, previous pharmaceutical approaches mostly failed due to unwanted side effects related to the structural similarities in between the multiple family members. Nevertheless, targeting of metalloproteinases still represents an interesting rational alone and in combination with other treatment modalities. Here, we will give an overview on the role of metalloproteinases in the irradiated tumor microenvironment and discuss the therapeutic potential of using more specific metalloproteinase inhibitors in combination with radiotherapy.